Amoxicillin/Clavulanic Acid-Induced Agranulocytosis: A Case Report and Review of the Literature - Aristides Armas Villalba; Marya Haq; Cunxian Zhang; Jinen Thakkar (Case Reports in Hematology)
Amoxicillin/clavulanic acid is one of the widely prescribed antibiotics in the outpatient setting giving excellent antimicrobial coverage and relatively safe profile in terms of adverse reactions. Gastrointestinal and cutaneous reactions are among the commonly reported. Our goal is to describe a case of agranulocytosis induced by amoxicillin/clavulanic acid in a previously healthy patient and review prior reports with similar presentation.